RETRACTED: Relating Sustainable Business Development Practices and Information Management in Promoting Digital Green Innovation: Evidence From China - Huang, Wen; Chau, Ka Yin; Kit, Ip Yun; Nureen, Naila; Irfan, Muhammad; Dilanchiev, Azer (Frontiers in Psychology, 2022)
Digital green innovations are being implemented in manufacturing to help organizations achieve sustainability by adopting sustainable development practices. However, little is known about the impact of the information management process on organizations’ digital green innovation. To address this gap, we devised a multidimensional framework based on the resource-based view (RBV) theory that serves as a basis for sculpting how the information management process captured and sustained organizational digital green innovation via sustainable development practices. 533 respondents from big and medium-sized manufacturing businesses in China were surveyed, and data were analyzed using the structural equation modelling (SEM) approach. The study makes numerous significant findings. Firstly, the sustainable development practice's dimensions (environment, economic, and social) are considerably improved by the information management process’ dimensions (acquisition, dissemination, and application). Secondly, sustainable development practices dimensions are critical for attaining organizations’ digital green innovation. Thirdly, sustainable development practices’ implementation mediates the linkage between the information management process and organizations’ digital green innovation. Our findings suggest that investing in and implementing cutting-edge technology and sustainable practices are critical for long-term success. Still, soft issues, such as organizational information management, are equally critical in today's information-based economy. Finally, in light of the study findings, we present theoretical and managerial implications.